2022
DOI: 10.3390/bios12121122
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Sensitivity Enhancement Based on Protonated Polyaniline Films Doped by Aluminum Nitrate

Abstract: Complex composite films based on polyaniline (PANI) doped hydrochloric acid (HCl) incorporated with aluminum nitrate (Al(NO3)3) on Au-layer were designed and synthesized as a surface plasmon resonance (SPR) sensing device. The physicochemical properties of (PANI-HCl)/Al(NO3)3 complex composite films were studied for various Al(NO3)3 concentrations (0, 2, 4, 8, 16, and 32 wt.%). The refractive index of the (PANI-HCl)/Al(NO3)3 complex composite films increased continuously as Al(NO3)3 concentrations increased. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…In addition, the line width (LW) of the recorded image decreased from 6 ± 1 pixels to 5 ± 1 pixels through using the Au-PAA layers, which indicates that the spatial resolution of the recorded image is enhanced. In our previous work [15], we used (PANI-HCl)/Al(NO3)3 Figure 6d demonstrates a local intensity of PSNP detected by the Au layer and Au-PAA layers as a function of the measurement time measured by WF-SPRM. The signal-to-noise ratio (S/N) of the Au-PAA layer is higher than the S/N of the Au layer, which is calculated by studying the line profile plot in the x-direction of the images (Figure 6e,f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the line width (LW) of the recorded image decreased from 6 ± 1 pixels to 5 ± 1 pixels through using the Au-PAA layers, which indicates that the spatial resolution of the recorded image is enhanced. In our previous work [15], we used (PANI-HCl)/Al(NO3)3 Figure 6d demonstrates a local intensity of PSNP detected by the Au layer and Au-PAA layers as a function of the measurement time measured by WF-SPRM. The signal-to-noise ratio (S/N) of the Au-PAA layer is higher than the S/N of the Au layer, which is calculated by studying the line profile plot in the x-direction of the images (Figure 6e,f).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the line width (LW) of the recorded image decreased from 6 ± 1 pixels to 5 ± 1 pixels through using the Au-PAA layers, which indicates that the spatial resolution of the recorded image is enhanced. In our previous work [15], we used (PANI-HCl)/Al(NO 3 ) 3 complex composite film as a coating for the Au layer to enhance the sensitivity of the WF-SPRM. We found that the S/N for Au-(PANI-HCl)/Al(NO 3 ) 3 with S/N of 10 ± 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conductive polymers have garnered attention from both scientific and industrial perspectives due to their exceptional optical, electrical, and electrochemical properties, as well as their facile processability, controllable chemical properties, and the ability to undergo reversible doping‐dedoping processes 1–3 . The optoelectrical properties of the conductive polymers are related to their conjugated nature and to the polarons formation, which is localized along the polymer chains because of the electron–phonon coupling 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymers have garnered attention from both scientific and industrial perspectives due to their exceptional optical, electrical, and electrochemical properties, as well as their facile processability, controllable chemical properties, and the ability to undergo reversible doping-dedoping processes. [1][2][3] The optoelectrical…”
Section: Introductionmentioning
confidence: 99%